2016
DOI: 10.1111/ijfs.13135
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcaria bifurcata: a key macro‐alga as a source of bioactive compounds and functional ingredients

Abstract: Summary The aim of this work was to study the proximate composition and the bioactive profile of Bifurcaria bifurcata. It contains 73.31 ± 0.69% of moisture, 8.57 ± 0.11 g per 100 g dry weight (d.w.) of protein, 5.81 ± 0.14 g per 100 g d.w. of lipid content and 30.15 ± 0.00 g per 100 g d.w. of ash. The polyunsaturated fatty acids were the most abundant fatty acid (FA), accounting for 2426.56 mg per 100 g which represents 41.77% of the total FA. The methanolic fraction showed high quantity of polyphenols (220.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
47
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 50 publications
11
47
4
Order By: Relevance
“…These results are in agreement with the data reported by Fleurence [ 18 ], who also noticed low protein content (<15 g/100 DW) in most of the brown seaweeds industrially exploited ( F. vesiculosus , A. nodosum , Laminaria digitata and Himanthalia elongata ). Similar values were found by Gómez-Ordoñez et al [ 14 ] and Alves et al [ 19 ] in B. bifurcata (10.92 g/100 DW and 8.57 g/100 g DW, respectively) and by Chan & Matanjun [ 17 ] in G. changii (12.57 g/100 DW). However, these values were lower than those obtained by Rodrigues et al [ 16 ] for brown (14.4–16.9 g/100 DW), red (20.2–23.8 g/100 DW) and green (18.8 g/100 DW) seaweed species.…”
Section: Resultssupporting
confidence: 88%
“…These results are in agreement with the data reported by Fleurence [ 18 ], who also noticed low protein content (<15 g/100 DW) in most of the brown seaweeds industrially exploited ( F. vesiculosus , A. nodosum , Laminaria digitata and Himanthalia elongata ). Similar values were found by Gómez-Ordoñez et al [ 14 ] and Alves et al [ 19 ] in B. bifurcata (10.92 g/100 DW and 8.57 g/100 g DW, respectively) and by Chan & Matanjun [ 17 ] in G. changii (12.57 g/100 DW). However, these values were lower than those obtained by Rodrigues et al [ 16 ] for brown (14.4–16.9 g/100 DW), red (20.2–23.8 g/100 DW) and green (18.8 g/100 DW) seaweed species.…”
Section: Resultssupporting
confidence: 88%
“…1 Bifurcaria bifurcata is a brown macroalga that thrives, year-round, in the intertidal areas (the lower shore, rockpools and mid-shore) along the coast of the Northern Atlantic, from Morocco (southern limit) to north-western Ireland (northern limit). [2][3][4] The chemical composition of this brown macroalga has gained particular attention, due to the abundance of a variety of acyclic diterpenes. [5][6][7][8][9][10][11][12] Compared to their cyclic counterparts, these linear diterpenes are relatively quite rare in nature, 2 yet quite interesting since a vast range of promising bioactivities have been recognized for them.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Compared to their cyclic counterparts, these linear diterpenes are relatively quite rare in nature, 2 yet quite interesting since a vast range of promising bioactivities have been recognized for them. 2,3,7,8,[13][14][15] Recently, Santos et al 5 demonstrated the antioxidant, anti-inammatory and antibacterial activities of B. bifurcata lipophilic extracts, mainly composed of linear diterpenes. In addition, a promising synergism was observed when these extracts were used together with antibiotic families of major clinical importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research into functional food ingredients has shown an interest in the development of foods containing seaweed or algal materials [ 14 , 15 ]. These materials have been part of the human diet since 600 BC [ 16 ] and they have a role of diet in sustaining human due to their diverse range of nutrients and bioactive compounds; such as polysaccharides, proteins, polyunsaturated fatty acids, minerals and significant amounts of antioxidants [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%